Provincial palm production analysis East Kalimantan 2016-2020 - Rahmawati, Siti (ProBisnis : Jurnal Manajemen, 2024)
This research aims to determine the influence of labor variables and land area on palm oil production in East Kalimantan Province. The dependent variable used is Palm Oil Production, while the independent variables used are Labor and Land Area. The data used in this research is secondary data which examines data for the 5 (five) year period 2016 – 2020 with districts/cities in East Kalimantan Province. The research method used is panel data regression analysis. The results of this research are that the Labor variable has a significant and positive effect on Palm Oil Production in 10 Regencies and Cities of East Kalimantan Province, and Land Area has a significant but negative effect on Palm Oil Production in 10 Regencies and Cities of East Kalimantan Province.